Diversity, tokenism, non-canonic music, And the crisis of the humanities in Academia in the United States (2017)
Taking as a starting point the question, should Latin American music have a greater presence in the courses of music history currently taught in the United States? This essay analyzes issues such as diversity and tokenism in the replication of the main models of knowledge production. These issues are analyzed in relation to the contemporary attack on the humanities in the American academy, in order to propose alternative approaches to education and academic work that function as critical models of the colonialist perspective that has informed musical education for generations and the neoliberal project that has been gradually imposed on the academy in the last twenty years.